Jesus outside the New Testament an introduction to the ancient evidence - Van Voorst, Robert E. (Grand Rapids, MI Eerdmans, 2000)
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- biography -- sources; Jesus Christ -- historicity